The moderating function of communication on the relationship between entrepreneurship orientation, learning orientation and international relationship trust - Md Daud Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Small and medium-sized enterprise exporters that build trusting relationships with foreign importers are strategically helpful in overcoming the challenges brought about by internationalization. Trust facilitates knowledge sharing between partners, and it allows small firms to expand their foreign market knowledge and consequently reduce their uncertainties that are caused by the unfamiliarity of international markets. Although building trust is central to fostering interorganizational relationships, limited research effort has been exerted on the process of developing and maintaining a trusting relationship. Based on resource-based view, this study assumes that capability in building international relationship trust is a function of organizational unique cultural orientations namely entrepreneurship orientation and learning orientation. Furthermore, the literature demonstrates that communication between partners moderates the relationship between entrepreneurship orientation and learning orientation, and relationship trust. Data was collected from small and medium business exporters in manufacturing sector. The sample consisted of 179 participants and data was analyzed using hierarchical moderated regression analysis. The results show that the relationship between learning orientation and trust is moderated by communication. In addition, the relationship between entrepreneurship orientation and trust is positive and significant. At the end of this paper, discussion, implications and limitations are presented.